Shifting Interfaces: An Anthology of Presence, Empathy and Agency in 21st-Century Media Arts, Hava Aldouby (ed.) (2020). Issue 2 (1st December 2020) - Heller, Lynne
Review of: Shifting Interfaces: An Anthology of Presence, Empathy and Agency in 21st-Century Media Arts, Hava Aldouby (ed.) (2020)Leuven: Leuven University Press, 332 pp., ISBN 978-9-46270-225-7, p/bk, $69.50